Pengaruh Tax Avoidance Terhadap Nilai Perusahaan: (Studi Pada Perusahaan Manufaktur yang Terdaftar Di BEI) - Sri Yuliandana; Junaidi Junaidi; Abid Ramadhan (Institut Bisnis dan Informatika Kesatuan, 2021)
Abstrack This study is a quantitative study that aims to the effect of tax avoidance on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The population in this study were manufacturing companies listed and listed on the Indonesia Stock Exchange for the 2014-2018 period, totaling 117 companies. The sampling technique in this study was purposive sampling, in order to obtain 25 sample companies. The method used in analyzing the effect of independent variables on the dependent in this study is panel data regression analysis using Eviews 10 software. The results show that tax avoidance has a negative and insignificant effect on firm value. This shows that the higher the tax avoidance done by the company, the lower the firm value. The limitation in this study is that it does not include elements of other variables outside of tax avoidance which may affect firm value. Keywords: Tax Avoidance, Firm Value, Indonesia Stock Exchange